Impact of Demonstrations on Improving Production and Income from Groundnut in Farmers’ Field of Purulia District of West Bengal - Kundu, Rajib; Biswas, Soma; Poddar, Ratneswar; Chatterjee, Souradeep (International Journal of Economic Plants, 2022)
Groundnut (Arachishypogaea) is an oilseed crop grown in West Bengal, India. These nuts are used as oil crops and grain legume crops. Most of the farmers cultivatethetraditional and age-oldvarieties. As a result, the production and productivity are relatively low when compared with that of the recently cultivated varieties. In West Bengal conditions, TG51 and TAG24 varieties are found suitable for small farmers. The present study was carried out in Purulia district of West Bengal. Total twenty-five (25) demonstrations was carried out in the farmers’ field as per the guidelines of All India Coordinated Research Project (ICAR-AICRP). The demonstrations were carried out duringthe 4 months of kharif season (July-October) in the year 2019. The collected data was tabulated and analyzed on the basis of range, mean and percentage Gaps at different percentage have been observed in different management practices like seed rate, seed treatment, fertilizer management and insecticide application. Farmers were motivated to follow new seed varieties and improved management practices. In demonstration fields, gross return increased by 48.80% and net return increased by 53.79% over the farmers’ fields. There was a 7.24% increase in benefit cost ratio. It is necessary to motivate farmers to adopt new technologies for future cultivation and this, in turn, would help to develop the socio- economic status of the farmers of this area.